LITERATURE REVIEW: STRATEGI KOMUNIKASI VISUAL DALAM MEMBANGUN PERSEPSI AUDIENS DI MEDIA SOSIAL INSTAGRAM - Icha Nur Lailatul Alfin; Putu Riana Artyanti Putri (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study aims to identify the visual communication strategies used in Instagram content and to understand how these strategies shape audience perception. The study employs a literature review approach by examining four international and six national articles published between 2021 and 2025. The literature search was conducted through Google Scholar using inclusion criteria that emphasize relevance to visual communication strategies, Instagram, visual communication, and audience perception. The data were analyzed using content analysis and thematic synthesis. The findings reveal five key strategies consistently identified across studies, namely message clarity, visual identity consistency, emotional appeal, contextual relevance, and differentiation. These strategies play an important role in enhancing audience understanding, building emotional connections, strengthening brand identity, and improving the effectiveness of message delivery on Instagram. The results of this review provide theoretical contributions by reinforcing the understanding of audience perception mechanisms within the context of digital visual communication, as well as practical contributions by highlighting the importance of consistent visual identity, authentic storytelling, and differentiation as guidance for content creators and digital practitioners in designing more effective and competitive content. Keywords: Instagram, Visual Communication, Audience Perception, Visual Communication Strategy, Visual Strategy